Ratings of the Long-Term Projects: New Approach - Filatova, T.V.; Brusov, P.N.; Orekhova, N.P.; Kulik, V.L. (Journal of Reviews on Global Economics, 2018)
The paper continues create a new approach to rating methodology: in addition to two papers, which have considered the creditworthiness of the non–finance issuers (Brusov et al., 2018c,d), we develop here a new approach to project rating. We work within investment models, created by authors. One of them describes the effectiveness of investment project from perspective of equity capital owners, while other model describes the effectiveness of investment project from perspective of equity capital and debt capital owners. The important features of current consideration as well as in previous studies are: 1) The adequate use of discounting of financial flows virtually not used in existing rating methodologies, 2) The incorporation of rating parameters (financial "ratios"), used in project rating, into considered modern investment models. Analyzing within these investment models with incorporated rating parameters the dependence of NPV on rating parameters (financial "ratios") at different values of equity cost k0, at different values of credit rates kd as well as at different values of leverage level L we come to very important conclusion, that NPV in units of NOI (NPV/NOI) (as well as NPV in units of D ((NPV/D) depends only on equity cost k0, on credit rates kd, on leverage level L as well as on one of the leverage ratios lj (on one of the coverage ratios ij ) and does not depend on equity value S, debt value D and NOI. This means that obtained results on the dependence of NPV (in units of NOI) (NPV/NOI) on leverage ratios lj (as well as on the dependence of NPV (in units of D) (NPV/NOI) on coverage ratios ij) at different equity costs k0, at different credit rates kd, at different leverage levels L carry the universal character: these dependencies remain valid for investment projects with any equity value S, any debt value D and any NOI.